2015
DOI: 10.1002/path.4538
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tumour suppressor PTEN expression in renal injury initiates SMAD3‐ and p53‐dependent fibrotic responses

Abstract: Deregulation of the tumour suppressor PTEN occurs in lung and skin fibrosis, diabetic and ischaemic renal injury. However, the potential role of PTEN and associated mechanisms in the progression of kidney fibrosis is unknown. Tubular and interstitial PTEN expression was dramatically decreased in several models of renal injury including aristolochic acid nephropathy (AAN), streptozotocin (STZ)-mediated injury and ureteral unilateral obstruction (UUO), correlating with Akt, p53 and SMAD3 activation and fibrosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 38 publications
8
55
0
Order By: Relevance
“…Previous research demonstrated that activation of proinflammatory cytokines contributed substantially to the development of renal interstitial fibrosis [13, 14]. Moreover, mounting evidence in vivo and in vitro has indicated that PTEN mediates multiple signal pathways involved in the pathophysiologic process of fibrosis in the kidney such as SMAD3, p53, and JNK[15, 16]. Here, we investigated the inhibition of PTEN activity by bisperoxovanadium (bpV) in post renal fibrosis induced by AKI with ischemia reperfusion (IR) models in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated that activation of proinflammatory cytokines contributed substantially to the development of renal interstitial fibrosis [13, 14]. Moreover, mounting evidence in vivo and in vitro has indicated that PTEN mediates multiple signal pathways involved in the pathophysiologic process of fibrosis in the kidney such as SMAD3, p53, and JNK[15, 16]. Here, we investigated the inhibition of PTEN activity by bisperoxovanadium (bpV) in post renal fibrosis induced by AKI with ischemia reperfusion (IR) models in mice.…”
Section: Introductionmentioning
confidence: 99%
“…43,46 PPM1A suppression further enhanced TGF-b1-induced SMAD3 phosphorylation and fibrotic gene expression, while PPM1A overexpression inhibited both responses. 45,46 Thus, these findings implicate PTEN as an upstream regulator of PPM1A function in dysfunctional tissue repair and establish PPM1A as a novel repressor of the SMAD3 fibrotic pathway. Stable silencing of PTEN, moreover, induced many of the same fibrotic genes as LPS or TGF-b1 (e.g., CTGF, PAI-1, vimentin, a-SMA, and fibronectin).…”
Section: Role Of Pten In Tlr4 Signalingmentioning
confidence: 98%
“…63 PTEN silencing induces dedifferentiation and cell cycle arrest, both biomarkers of maladaptive repair, and cooperates with TGF-b1 to further stimulate expression of the fibrotic signature genes CTGF, PAI-1, vimentin, a-SMA, and EDA-fibronectin. 45,46 The mechanism of PTEN downregulation in the context of fibrosis is not known but is likely the result of increased TGF-b1 levels in the injury microenvironment. TGF-b1 reduces, moreover, the levels of the C-terminal SMAD2/3 protein phosphatase PPM1A, a terminator of TGF-b1 signaling.…”
Section: Role Of Pten In Tlr4 Signalingmentioning
confidence: 99%
See 2 more Smart Citations